Chính sách tiền tệ và quy tắc Taylor: Nghiên cứu thực nghiệm tại một số quốc gia Đông Nam Á - Nguyen Ha , Thach (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
Using a forward-looking Taylor rule, the paper aims to study the behaviour of the central bank’s on the monetary policy conducting in a group of developing countries in Southeast Asian. The results show that a linear Taylor rule is consistent in explaining monetary policy in Indonesia, Malaysia, Philippines, Thailand, and Vietnam. In addition, using the smooth transition regression model with the expected inflation variable, the results indicate that the monetary behaviour of the Central Bank in Indonesia, Malaysia, and the Philippines can be described by a nonlinear Taylor rule while in Vietnam and Thailand, there is no evidence of nonlinearity on the conduct of monetary policy.
Keywords: Monetary policy; Taylor rule; Nonlinear; Southeast Asian